A Case Report of Incontinentia Pigmenti in a Newborn with Positive Family History Extending Over Three Generations - Seyedeh Fatemeh Khatami; Pouya Parvaresh; Abbas Boskabadi; Hassan Boskabadi; Gholamali Mamori (Mashhad University of Medical Sciences, 2017)
Background: Incontinentia pigmenti (IP), also known as Bloch-Sulzberger syndrome, is a rare X-linked dominant genodermatosis that presents at the time of birth or soon after birth with cutaneous manifestation. This disorder may also affect the ectodermal tissues, such as the central nervous system, skeletal system, eyes, hair, nails, and teeth. The dermatological findings occur in four successive phases.Case report: Herein, we presented the case of a two day-old female newborn with inflammatory vesiculopustular lesions on the right forearm and lower limbs, who was in a good general condition. The patient had a history of similar disease in three other members of her family, who had dental abnormalities as the most common non-cutaneous manifestation. This case report highlighted the importance of a detailed diagnostic workup for the newborns with pustular skin disease.Conclusion: IP is a rare, x-linked dominant genodermatosis with multiple organs involvement. Dermatological abnormalities are the most prominent manifestation. The diagnosis is based on the clinical findings, the presence of positive family history of skin vesiculopustular lesions support the diagnosis. The skin lesions do not require specific treatment and prognosis depend to other organs involvement.